Schistosoma mansoni Soluble Egg Antigens Enhance Listeria monocytogenes Vector HIV-1 Vaccine Induction of Cytotoxic T Cells - Bui, Cac T. (American Society for Microbiology, 2014)
Vaccines are an important public health measure for prevention and treatment of diseases. In addition to the vaccine immunogen, many vaccines incorporate adjuvants to stimulate the recipient's immune system and enhance vaccine-specific responses. While vaccine development has advanced from attenuated organism to recombinant protein or use of plasmid DNA, the development of new adjuvants that safely increase immune responses has not kept pace. Previous studies have shown that the complex mixture of molecules that comprise saline soluble egg antigens (SEA) from Schistosoma mansoni eggs functions to promote CD4(+) T helper 2 (Th2) responses. Therefore, we hypothesized that coadministration of SEA with a Listeria vector HIV-1 Gag (Lm-Gag) vaccine would suppress host cytotoxic T lymphocyte (CTL) and T helper 1 (Th1) responses to HIV-1 Gag epitopes. Surprisingly, instead of driving HIV-1 Gag-specific responses toward Th2 type, we found that coadministration of SEA with Lm-Gag vaccine significantly increased the frequency of gamma interferon (IFN-γ)-producing Gag-specific Th1 and CTL responses over that seen in mice administered Lm-Gag only. Analysis of the functionality and durability of vaccine responses suggested that SEA not only enlarged different memory T cell compartments but induced functional and long-lasting vaccine-specific responses as well. These results suggest there are components in SEA that can synergize with potent inducers of strong and durable Th1-type responses such as those to Listeria. We hypothesize that SEA contains moieties that, if defined, can be used to expand type 1 proinflammatory responses for use in vaccines.